Educational reconstructions of quantum physics using the sum over paths approach with energy dependent propagators - Malgieri, Massimiliano; Onorato, Pasquale (Journal of physics. Conference series, 2021)
Moving from the research tradition on the use of Feynman’s sum over paths approach in education, we have developed an educational reconstruction of elementary quantum physics which uses Feynman paths at fixed energy and is capable of a simple conceptual explanation of discrete energy levels in bound systems. The reconstruction has been found to offer several educational advantages, may help students think of quantum physics in a way more akin to how the subject is used by scientists, and allows to shed light on the relationship between energy and time.